2010
DOI: 10.1016/j.ejcnurse.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Telephone Interventions for People with Cardiac Disease: A Review of the Research Literature

Abstract: The results suggest that people with cardiac disease showed some benefits from nurse-led/delivered telephone interventions. More rigorous research into this area is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
(378 reference statements)
1
20
0
2
Order By: Relevance
“…As well, Stolic et al found that people with cardiac disease benefit from nurse-led/delivered telephone interventions. 19 However, another study by Jaarsma et al which investigated the impact of educational and supportive interventions on the quality of life and the ability to self-care of the patients with cardiac failure did not find any significant difference between the control group and the intervention group 3 months after the operation. They asserted that the tools employed in his study to assess patients' ability to self-care had been devised to be used for patients with any type of heart disease and not specifically for those with cardiac failure.…”
Section: Discussionmentioning
confidence: 96%
“…As well, Stolic et al found that people with cardiac disease benefit from nurse-led/delivered telephone interventions. 19 However, another study by Jaarsma et al which investigated the impact of educational and supportive interventions on the quality of life and the ability to self-care of the patients with cardiac failure did not find any significant difference between the control group and the intervention group 3 months after the operation. They asserted that the tools employed in his study to assess patients' ability to self-care had been devised to be used for patients with any type of heart disease and not specifically for those with cardiac failure.…”
Section: Discussionmentioning
confidence: 96%
“…As Stolic et al suggest [1], we agree there is increasing evidence that non-acute management of coronary heart disease by telephone in addition to standard medical care is a viable supplement or alternative to facility-based cardiac rehabilitation for patients with disease. Further, the relatively low cost of telephone-based interventions make them an attractive option to support patients and to deliver education in the early post-discharge period.…”
mentioning
confidence: 88%
“…In addition, elderly patients participate less frequently in cardiac rehabilitation [3] although they present more adverse health outcomes than do younger patients who have been diagnosed with CHD [5]. Several studies have shown that case management can reduce hospitalization and increase quality of life, but only a few studies have focused on patients with acute myocardial infarction (AMI) and elderly patients [4,[6][7][8]. Moreover, studies evaluating the cost-effectiveness of case management are scarce and have not considered long-term effects and costs.…”
Section: Introductionmentioning
confidence: 99%